Drop-out determinants that influence the out-of-school youth in Iligan City and Lanao Del Norte in the Philippines - Dumadag, Christopher T; Silor, Adelfa C; Capuno, Gemma Grace D.; Cortez-David, Sigritch (International Journal of Innovative Research and Scientific Studies, 2023)
The youth represent a significant source of hope for a developing country such as the Philippines. Adolescents show a lack of interest in pursuing education leading to high dropout rates. Many researchers have conducted several studies to determine why students stop schooling. This study aimed to investigate the dropout determinants that influence out-of-school youth in Iligan City and Lanao Del Norte. Purposive sampling was used. Two hundred (200) out-of-school youth from Iligan City and Lanao Del Norte were the participants of this study. The researchers used a Likert scale survey questionnaire to collect the data. In addition, the researcher used descriptive analysis to calculate the median and frequency. The results found that academic experience especially boredom in the classroom was the leading dropout determinant influencing out-of-school youth. The other factor was family financial support. The study recommends that the government, non-government organizations and all stakeholders not only focus on providing financial assistance to students but also consider the students’ learning experience inside the classroom. Academic boredom is a serious issue that requires immediate solutions.